المفاهيم المنهجية للبحت العلمي في مجال العمارة والتخطيط (Journal of Building and Road Research, 2021)
Scientific research is a systematic faculty of human mind, oriented to solve a livable problem, or to explain a phenomenon, in order to enable scientific reasoning to derive solutions to the problem, or to explain correlations and causality of the phenomenon. Methodology, therein, provides the necessary logical consequence of deploying adequate and relevant processes. Deductive method, emanating from positivism, hegemonies the scientific sphere till Einstein proofed the insufficiency of empiricism to cope with the contemporary advance of science.The traditional logic of science is proved to deter the prevailing creative and innovative trends. This paper tends to scrutinize theramifications of this complicated situation on the field of architecture and planning, aiming to highlight the dilemma facing the research methodologywithin the field, in a way to grope the directions of the expected paradigm shift. The criticisms casted to conventional methods of research have negatively affected that of the architecture and planning field, which suffers an ultimate inconsistency, since the field is composed of three, paradoxically, heterogeneous scientific components of: pure science, social science and art. The analysis of the paper tends to prove validity of the hypothetical deduction methodology, originated from rational criticism, to formulate the theoretical background to the new paradigm. It recommends the critical analysis method as atabula rasafor synthesizingand evaluating urban issues, while urban context and urban scape are called to circumscribe research on phenomena to their socioeconomic and sociospatial context.Urban scape is moreover utilized as a tool for analysis and evaluation
Keywords: scientific research; research methodological concepts; induction inference; deduction inference; critical analysis; hypothetical deduction